The Usage of Chitosan from Shrimp Waste as Natural Preservative for Fish Cilok (Traditional Food in Indonesia) - H.B.A Jayawardana; Ahmad Afandi (Indonesian Journal of Science and Education (IJOSE), 2019)
Cilok is one of the traditional food in Indonesia. Cilok is a popular treat among Indonesians due to its good taste and cheap price. To make it last longer, cilok is sometimes added with preservative. However, such attempt will endanger consumers if dangerous preservatives are used, such as formaldehyde and borax. Their usage in food preservation may negatively impact consumers’ health. The aim of this research was to develop an alternative, natural preservative for fish cilok. The preservative would be chitosan. The method used is an experiment that is by making a chitosan solution from the shrimp skin waste. In the experiment, chitosan was extracted from shrimp waste. A 1,5% chitosan concentrate was used. Its preservation potency was tested by giving three treatments towards fish cilok: fish cilok with 1,5% chitosan coating; fish cilok mixed with 1,5% chitosan solution and fish cilok without chitosan. The three treatments were observed and an organoleptic test was performed according to the preservation time in a room temperature on Day 1, 2, 3, 4 and 5. The parameters tested during the experiment were taste, color, odor and texture of fish cilok. The research results showed that fish cilok coated with 1,5% chitosan solution lasted longer than fish cilok without or added with chitosan. Keywords: chitosan, natural preservative, fish cilok